Dietary Supplementation With Chlorogenic Acid Derived From Lonicera macranthoides Hand-Mazz Improves Meat Quality and Muscle Fiber Characteristics of Finishing Pigs via Enhancement of Antioxidant Capacity - Wang, Wenlong; Wen, Chaoyue; Guo, Qiuping; Li, Jianzhong; He, Shanping; Yin, Yulong (Frontiers in Physiology, 2021)
Chlorogenic acid (CGA), one of the most abundant polyphenol compounds in nature, is regarded as a potential feed additive to promote animal health and enhance the meat products’ quality via its various biological properties. The current study aims: (1) to determine whether dietary CGA supplementation improves meat quality and muscle fiber characteristics, and (2) to ascertain whether the corresponding improvement is associated with enhancing the antioxidant capacity of the finishing pigs. Thirty-two (Large × White × Landrace) finishing pigs with an average initial body weight of 71.89 ± 0.92 kg were allotted to 4 groups, and each was fed diets supplemented with 0, 0.02%, 0.04%, or 0.08% (weight/weight) of CGA. The meat quality traits, muscle fiber characteristics, and the serum and muscle antioxidant capacity were assessed. Results suggested that, compared with the control group, dietary CGA supplementation at a level of 0.04% significantly decreased the b* value and distinctly increased the inosinic acid content and of longissimus dorsi (LD) and biceps femoris (BF) muscles (P < 0.01). Moreover, dietary supplementation with 0.04% of CGA markedly improved the amino acid composition of LD and BF muscles, as well as augmented the mRNA abundance of Nrf-2, GPX-1, MyoD, MyoG, and oxidative muscle fiber (Ⅰ and Ⅱa) in LD muscle (P < 0.05). This result indicates that a diet supplemented with 0.04% of CGA promotes myogenesis and induces a transformation toward more oxidative muscle fibers in LD muscle, subsequently improving meat quality. Besides, dietary supplementation with 0.02% and 0.04% of CGA notably enhanced the serum GSH-PX level (P < 0.01). Considering all these effects are closely related to the alteration of antioxidant activities of the finishing pigs, the underlying metabolism is likely connected to the boosting of their antioxidant capacity induced by dietary CGA.